Interferoids: In vitro and in vivo conversion of native interferons to lower molecular weight forms - Stewart, William E. (1978)
Mouse interferons appear as two distinct molecular forms, one migrating at 38,000 daltons in sodium dodecyl sulfate/polyacrylamide gels and one migrating at 22,000 daltons; these interferons comprise about 80% and 20% of total activities, respectively. When such interferon preparations are briefly exposed to acidic periodate buffer, the larger interferon species is apparently converted to the smaller form since the activity at 38,000 daltons is completely eliminated while the activity at 22,000 daltons increases significantly; upon further oxidative cleavage, antiviral activity becomes detectable migrating at 15,000 daltons. Because no native mouse interferon has been reported as such small molecules, this antiviral activity is designated mouse “interferoid” to distinguish it from the native, naturally occurring interferon forms. Prolonged acidperiodate treatment fails to quantitatively convert the 22,000-dalton interferon to the 15,000-dalton interferoid since both are inactivated. When L cells are induced to make interferon in the presence of glycosylation inhibitors, either D-glucosamine or 2-deoxy-D-glucose, they produce approximately normal levels of antiviral activity. However, when such preparations are analyzed by sodium dodecyl sulfate/polyacrylamide gel electrophoresis, little activity (<10%) migrates as either the 38,000-dalton or 22,000-dalton native interferons. The interferons and interferoid are antigenically and hydrophobically indistinguishable. These data suggest that induced mouse cells normally synthesize the interferoid as a precursor polypeptide that is either partially or extensively modified by carbohydrate additions to produce, respectively, the 22,000- and 38,000-dalton mouse interferons. Because interferoid is apparently fully biologically active without these moieties, chemical synthesis of such unmodified polypeptides or active fragments from them appears feasible.